Handbook of research on secure multimedia distribution - Lian, Shiguo; Zhang, Yan 1977-. (Hershey, PA Information Science Reference, 2009)
"This handbook is for both secure multimedia distribution researchers and also decision makers in obtaining a greater understanding of the concepts, issues, problems, trends, challenges and opportunities related to secure multimedia distribution"--Provided by publisher.
Prof. Rhandley Cajote (recommending faculty)
Keywords: Multimedia systems -- Security measures -- United States; Data protection -- United States; Copyright and electronic data processing -- United States